Persistence to oral 5-aminosalicylate therapy for inflammatory bowel disease in Australia. (March 2014) - Selinger, Christian P; Kemp, Andrew; Leong, Rupert WL
<x xml:space="preserve">Abstract</x> Aminosalicylate (5-ASA) is effective treatment for inflammatory bowel diseases (IBDs) but requires continuous maintenance therapy. This study determines persistence of 5-ASA in IBD using national population-based data for Australia from 2002 to 2011 with follow up for 36 months. Non-persistence was defined as failing to fill a prescription for 3 months. Of 12, 592 patients those initiated on non-sulphasalazine 5-ASA (2917) had significantly higher persistence (P < 0.001) than those on sulphasalazine (9675). Persistence for sulphasalazine and non-sulphasalazine 5-ASA initiation was 22.3% and 28.5% at 12-months, and 11.9% and 16.2% at 24-months. Sulphasalazine poor persistence continued despite intra-class switch to another 5-ASA. Patients receiving immunomodulator co-therapy had higher persistence (P < 0.001). National population-based data identified persistence to 5-ASA to be low but significantly lower when sulphasalazine is the initial drug. Physicians should stress the importance of long-term 5-ASA therapy as overall drug efficacy especially the 5-ASA chemo-prophylactic benefits may be reduced by non-persistence.